An Optimization of (Q, r) Inventory Policy Based on Health Care Apparel Products with Compound Poisson Demands. (28th September 2014) - Pan, An; Hui, Chi-Leung; Ng, Frency
Abstract : Addressing the problems of a health care center which produces tailor-made clothes for specific people, the paper proposes a single product continuous review model and establishes an optimal policy for the center based on ( Q, r ) control policy to minimize expected average cost on an order cycle. A generic mathematical model to compute cost on real-time inventory level is developed to generate optimal order quantity under stochastic stock variation. The customer demands are described as compound Poisson process. Comparisons on cost between optimization method and experience-based decision on Q are made through numerical studies conducted for the inventory system of the center.